1999
DOI: 10.1016/s0925-8388(98)01006-8
|View full text |Cite
|
Sign up to set email alerts
|

DMSO-induced dehydration of DPPC membranes studied by X-ray diffraction, small-angle neutron scattering, and calorimetry

Abstract: The influence of dimethyl sulfoxide (DMSO) on membrane thickness, multilamellar repeat distance, and phase transitions of 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) was investigated by X-ray diffraction and small-angle neutron scattering (SANS). The differential scanning calorimetry (DSC) study of water freezing and ice melting was performed in the ternary DPPC /DMSO /water and binary DMSO /water systems. The methods applied demonstrated the differences in membrane structure in three sub-regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(104 citation statements)
references
References 10 publications
6
96
2
Order By: Relevance
“…The small-angle neutron scattering experiments (SANS) with unilamellar vesicles were carried out at YuMO spectrometer in Dubna, Russia [1,2,16]. The model of infinitely thin sphere was applied for the interpretation of the SAXS curves in the region of scattering vector q from 0.005Å -1 to 0.04Å -1 [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small-angle neutron scattering experiments (SANS) with unilamellar vesicles were carried out at YuMO spectrometer in Dubna, Russia [1,2,16]. The model of infinitely thin sphere was applied for the interpretation of the SAXS curves in the region of scattering vector q from 0.005Å -1 to 0.04Å -1 [3].…”
Section: Methodsmentioning
confidence: 99%
“…The structure and properties of phospholipids membranes, as they serve as a simple and appropriate model for biological membranes, are investigated intensively by X-ray and neutron scattering techniques [1][2][3][4]8,9,16,19]. The structural investigation of drug delivery systems based on the lipid vesicles (liposomes) is a perspective direction for SR application [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Guinier approximation of SANS spectra was used for the calculation of membrane thickness of egg yolk phosphatidylcholine vesicles (d l =41.7Å at 20 o C), dipalmitoylphosphatidylcholine (DPPC) vesicles (d l =49.6Å at 20 o C), and mixed lipid/surfactant vesicles [6][7][8]. A strip-function model of evaluating SANS curves was developed recently which allows to determine important membrane parameters describing the geometry and hydration of large oligolamellar vesicles [9].…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of DMSO above 10 mol% (1 DMSO molecule per 9 water molecules) at 25°C induce a subgel phase (14), which is characterized by different head group ordering. Small-angle X-ray and neutron scattering studies (15)(16)(17) have shown that DMSO substantially decreases the solvent gap thickness (equilibrium separation) between lamellae of both gelphase and fluid PC multilamellar vesicles. Explanations for the phase behavior and equilibrium separation phenomena often implicate some mechanism of head group dehydration/ desolvation brought about by DMSO (14,16,18).…”
mentioning
confidence: 99%